HBR Guide to Buying A Small Business - Ruback, Richard S. (Havard Business Review Press, 2017)
This book takes a big idea from our popular courses at the Harvard Business School and for the first time shares it beyond cmapus. The big idea is that you can buy an existing small business, right now, and run it as a CEO.